2009
DOI: 10.1074/mcp.m800340-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-based Identification of Novel Factor Inhibiting Hypoxia-inducible Factor (FIH) Substrates Indicates Widespread Asparaginyl Hydroxylation of Ankyrin Repeat Domain-containing Proteins

Abstract: Post-translational hydroxylation has been considered an unusual modification on intracellular proteins. However, following the recognition that oxygen-sensitive prolyl and asparaginyl hydroxylation are central to the regulation of the transcription factor hypoxia-inducible factor (HIF), interest has centered on the possibility that these enzymes may have other substrates in the proteome. In support of this certain ankyrin repeat domain (ARD)-containing proteins, including members of the IB and Notch families, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
180
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(190 citation statements)
references
References 29 publications
9
180
1
Order By: Relevance
“…The false positive rate (FPR) of the algorithm for identification was set to 4% with a randomized database, appended to the original one. Only those proteins with 50% or more probability to be present in the mixture and detected with a score above 20, as calculated by the software, were selected for proteomic analysis (29). Data sets were normalized using the "autonormalization" function of PLGS, and label-free quantitative analysis was performed by comparing the normalized peak area/intensity of the peptides identified.…”
Section: Methodsmentioning
confidence: 99%
“…The false positive rate (FPR) of the algorithm for identification was set to 4% with a randomized database, appended to the original one. Only those proteins with 50% or more probability to be present in the mixture and detected with a score above 20, as calculated by the software, were selected for proteomic analysis (29). Data sets were normalized using the "autonormalization" function of PLGS, and label-free quantitative analysis was performed by comparing the normalized peak area/intensity of the peptides identified.…”
Section: Methodsmentioning
confidence: 99%
“…Significantly, proteins containing the ankyrin repeat domain (ARD) such as Notch are other substrates for FIH-1 (8). Moreover, the binding affinity of FIH-1 for Notch 1 is appreciably greater than for HIF-1α (8,10). With respect to Notch 1, FIH-1 hydroxylates the Notch ICD at two asparagine residues (N 1945 and N 2012 ) (11).…”
mentioning
confidence: 99%
“…The asparaginyl hydroxylase factor inhibiting HIF-1α (FIH-1) can negatively regulate Notch signaling (8). FIH-1 was originally identified as a protein that interacts with and inhibits the activity of HIF-1α in the C-terminal transactivation domain (CAD) (9) by coupling the oxidative decarboxylation of 2-oxoglutarate to the hydroxylation of HIF-1α (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While prolyl hydroxylation data are missing in this study, other factors of the NF-B signalling pathway (I B , I B and p105) have been shown to be efficiently hydroxylated by FIH [94,95]. However, no functional alterations in the NF-B pathway could be identified following asparaginyl hydroxylation.…”
Section: Ikkmentioning
confidence: 64%